Code-switching as a marked socio-pragmatic discourse strategy in Nigerian police interrogation - Adegbite, Matthew (2023)
Police-suspect interrogation is a strategically adversarial engagement that involves tactical deployment of a variety of discourse strategies. This situation becomes more complex in a multilingual context like Nigeria where the interlocutors have the opportunity of expressing their communicative intents in a multiplicity of codes. This paper focuses on the pragmatic ways code-switching (CS) is deployed by interrogators and suspects as a socio-pragmatic discourse strategy to achieve their institutional and personal goals. We will see that CS is used persuasively, as interrogators and suspects negotiate from positions of power and inferiority, drawing on socio-cultural norms and expectations. 30 audio-recorded interrogations at the Ọ̀̀yọ́ and Oǹdó state commands of the Nigeria Police form the primary data. All the interrogations were conducted primarily in Nigerian English and the subjects were 18 years or above. Critical Discourse Analysis and Communication Accommodation Theory are adopted for analysis and discussion. Findings show that code-switching is employed with different effects for different participants: for interrogators to warn, threaten, and perform verbally aggressive acts that attack suspects’ self-worth; for suspects to plead for mercy and to blame-shift; and for both to boost credibility and authority, and to highlight socio-cultural shared knowledge. Swearing and cursing also take place within CS with suspects using self- and other-cursing to indicate sincerity and to try to persuade interrogators to believe their claims and interrogators swearing to express their commitment and determination to follow through with a course of action. CS is, therefore, seen as a marked and strategic communicative alignment that is motivated by institutional and personal goals and used for persuasive purposes.